Eksplorasi Jamur Entomopatogen, Dari Beberapa Rizosfer Tanah, Dengan Insect Bait Method - Sudiarta, I Putu; Syahbana , Raditya Darmawan; Yuliadhi, Ketut Ayu; Suputra, I Putu Wirya; Gargita, I Wayan Diksa (AGRICA, 2024)
This study aims to identify the types of entomopathogenic fungi obtained from the exploration results of the insect bait method in rhizosphere soil samples from several locations in the Bedugul area, Bali. The exploration results showed differences among the three soil samples, where the Pakcoy cultivation soil sample showed infected insect baits with Metarhizium sp. fungi. In contrast, in the Danau Buyan and Bedugul Botanical Garden soil samples, symptoms of infestation were not infected by fungi. Koch's postulate test confirmed the presence of entomopathogenic fungi in the Pakcoy cultivation soil sample, which was later identified morphologically and microscopically as Metarhizium. This study contributes to understanding the ecology of entomopathogenic fungi in the context of biological pest control, especially in sustainable agriculture.